2020
DOI: 10.7717/peerj.9201
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis reveals a metabolic ten-gene signature in hepatocellular carcinoma

Abstract: Background Due to the complicated molecular and cellular heterogeneity in hepatocellular carcinoma (HCC), the morbidity and mortality still remains high level in the world. However, the number of novel metabolic biomarkers and prognostic models could be applied to predict the survival of HCC patients is still small. In this study, we constructed a metabolic gene signature by systematically analyzing the data from The Cancer Genome Atlas (TCGA), Gene Expression Omnibus (GEO) and International Cancer Genome Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…Several prior analyses have also shown that certain gene signatures may predict patient survival (20)(21)(22)(23)(24)(25)(26); however, our study has some differences and/or advantages compared with similar analyses. First, the gene signatures built in previous studies require many genes (20)(21)(22)(23), which possibly leads to some difficulties in real-world practice. Our novel signature requires only 4 genes, and the predictive ability of our signature is acceptable, which increases the feasibility of the use of our signature in real-world practice.…”
Section: Discussionmentioning
confidence: 80%
“…Several prior analyses have also shown that certain gene signatures may predict patient survival (20)(21)(22)(23)(24)(25)(26); however, our study has some differences and/or advantages compared with similar analyses. First, the gene signatures built in previous studies require many genes (20)(21)(22)(23), which possibly leads to some difficulties in real-world practice. Our novel signature requires only 4 genes, and the predictive ability of our signature is acceptable, which increases the feasibility of the use of our signature in real-world practice.…”
Section: Discussionmentioning
confidence: 80%
“…Most of the genes have been proved to take part in pathogenesis, progression and prognosis of cancers. We compared this metabolic risk model with other metabolic signatures in previous studies and found that PAFAH1B3 is a good prognostic gene in myelogenous leukemia 26 while LPCAT1 is a risky prognostic gene in hepatocellular carcinoma 27 , which has the same function in colon cancer. Platelet activating factor acetyl hydrolase 1B3 (PAFAH1B3) is involved in ether lipid metabolism, and was reported to play an important role in tumorigenesis and aggressiveness in many different cancers 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the identification of prognostic gene signature for HCC has been noted in many researches ( Chen et al, 2020 ; Hu et al, 2020 ; Zhu et al, 2020 ). However, to the best of our knowledge, none of them constructed a risk signature based on IRGs related to CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%